Evaluation of a training course in infection control for nurses. - Picheansatian W. (2014)
OBJECTIVE: To evaluate the effectiveness of a training course in infection control for nurses. MATERIAL AND METHODS: A quasi-experimental study was performed from November 1, 2001 to December 31, 2002. The study was divided into three phases; 1) pre-intervention (November 1-30, 2001) to survey baseline data among participants, 2) intervention (January 1-31, 2002) to establish, develop and conduct the training course, 3) post-intervention (February 1, 2002 to December 31, 2002) to evaluate the effectiveness of the training program, and conduct a workshop for infection control project presentations. The research instruments consisted of questionaires and a focus group discussion guide. RESULTS: Forty-six nurses who had experience of working as infection control nurses (ICN) for more than one year and 46 hospital administrators were enrolled in the pre-interventional phase. Major problems identified among ICNs were inadequate knowledge, multiple simultaneous job descriptions, overwork and lack of collaboration from colleagues. After intervention, significant improvement was observed on their knowledge and confidence among ICNs (rating scale, 4.09 vs. 3.43; p< 0.001). All administrators agreed that the training course was beneficial to ICNs and believed that the problems in practices of IC would be solved. More satisfaction of ICNs among hospital administrators was also observed (97.7% vs. 28.3%; p< 0.001). CONCLUSION: The present study suggested that the training course to provide practical knowledge for ICNs be effective and should be conducted periodically to keep up with the advance in medical technology. An ICN network with other academic institutions should be established.